(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tripura, the second-smallest state in India’s northeast, is characterized by hills and uplands, with only 19.8% plains across its 10,491 square km area. The diverse tribal population includes nineteen ethnic groups, each with distinct languages and cultural traditions. Despite the rich cultural diversity, there is a lack of documentation on rice beer preparation by the Tripuri tribes. This paper aims to fill that gap by identifying traditional ingredients and methods for rice beer preparation. The study selected respondents from six districts in Tripura, focusing on areas with a significant Tripuri tribal population. A random survey involved informal interactions to ensure understanding of the local language. The methodology employed direct observation to document the traditional preparation methods, exploring the socioeconomic values and traditions associated with rice beer. The main objectives of the study are to identify traditional ingredients and methods used by the Tripuri tribe in rice beer preparation. The results reveal two primary methods: chuwan preparation and rice-beer preparation. The paper contributes valuable insights into the cultural practices of the Tripuri tribes, shedding light on their traditional knowledge of fermented alcoholic beverages, particularly rice beer. The implementation of food science interventions, such as optimizing preparation methods, improving hygiene standards, and enhancing packaging, holds the potential to create a profitable local business in this sector and attract consumers from across the country.